2018
DOI: 10.1186/s12913-018-3789-z
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism exposures and outcomes amongst hospital doctors and nurses: a systematic review

Abstract: BackgroundPresenteeism is a behavior in which an employee is physically present at work with reduced performance due to illness or other reasons. Hospital doctors and nurses are more inclined to exhibit presenteeism than other professional groups, resulting in diminished staff health, reduced team productivity and potentially higher indirect presenteeism-related medical costs than absenteeism. Robust presenteeism intervention programs and productivity costing studies are available in the manufacturing and busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 55 publications
(193 reference statements)
4
86
0
4
Order By: Relevance
“…Therefore, it is possible that there was sample bias with participants who had more experiences with presenteeism were more likely to participate, especially in responding to these three optional questions. However, our study's findings echoed what has been described by occupational health and business scholars as reasons for presenteeism in other industries and the consequences were similar to other studies of nurse presenteeism consequences (Brborović et al, ; Letvak et al, ; Lui, Andres, & Johnston, ). Another limitation of this study was that the questions were asked in a survey which did not allow for follow‐up questions to clarify.…”
Section: Limitationssupporting
confidence: 91%
“…Therefore, it is possible that there was sample bias with participants who had more experiences with presenteeism were more likely to participate, especially in responding to these three optional questions. However, our study's findings echoed what has been described by occupational health and business scholars as reasons for presenteeism in other industries and the consequences were similar to other studies of nurse presenteeism consequences (Brborović et al, ; Letvak et al, ; Lui, Andres, & Johnston, ). Another limitation of this study was that the questions were asked in a survey which did not allow for follow‐up questions to clarify.…”
Section: Limitationssupporting
confidence: 91%
“…Workers without access to paid leave have higher rates of presenteeism, and are less likely to receive preventative health services such as getting flu shots [22]. Occupational sector also influences rates of presenteeism, with studies from various countries showing higher rates of presenteeism among workers in healthcare, public service, and educational sectors, as these essential services often do not have substitute workers available [23][24][25]. Indeed, a recent systematic review identified occupation type as one of the strongest predictors of presenteeism [2].…”
Section: Discussionmentioning
confidence: 99%
“…They make it difficult to compare the results regarding prevalence. Furthermore the sociocultural distinctions and the various health systems complicate comparisons between countries [27].…”
Section: Introductionmentioning
confidence: 99%